The Influence of Service Quality As A To Total of Quality Management (Study In Badan Pertanahan Nasional Office Yogyakarta) - Winarno, Wahyu Handayani, Wisnalmawati & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
One of the important tasks of the Ministry of ATR/BPN is to carry out theintegrated and integrated Land Resources Management by utilizing thedevelopment of modern information and management system technology. Thisresearch aims to: 1. analyze Total Quality Management that directly affects theapplicantâs satisfaction, 2 Total Quality Management influence on the requestersatisfaction mediated by Service Quality. Subjects in this research are applicantsâsatisfaction of Pertanahan Office Yogyakarta. The sample uses as many as onehundred respondents, data analysis technique uses Structural Equational Model(SEM) with SmartPLS Program. The results of this research prove: 1. analyzeTotal Quality Management that directly affects the requester satisfaction, 2. TotalQuality Management Total Quality Management influence on the requestersatisfaction mediated by Service Quality. The findings of this study may contributeto consumer behaviour models, in Badan Pertanahan Nasional (BPN) officeYogyakarta and Tripple duties of Higher Education.